1989
DOI: 10.1161/01.cir.80.4.983
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of improved ischemic regional dysfunction by bradycardia. Studies on UL-FS 49 in swine.

Abstract: In anesthetized swine, the left anterior descending coronary artery was cannulated and perfused at constant blood flow levels during two grades of ischemia. In one group (n = 10), moderate ischemia reduced percent systolic wall thickening (by sonomicrometry) from 25+±7% to 6±2%, whereas in the other group (n =7), severe ischemia reduced percent wall thickening from 24+6% to -0.5+4%. Heart rate was paced in both groups at 91 beats/min. After reperfusion and complete return to control conditions, administration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
45
1
2

Year Published

1991
1991
2009
2009

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 39 publications
0
45
1
2
Order By: Relevance
“…11 A possible direct effect of the specific bradycardiac drug UL-FS 49 on diastolic events cannot be excluded. However, the action of the drug to selectively suppress the sinus node rate, and other data demonstrating no direct effect on myocardial contractility and systolic events, [16][17][18][19] suggest that UL-FS 49 may not have important direct effects on diastolic properties.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…11 A possible direct effect of the specific bradycardiac drug UL-FS 49 on diastolic events cannot be excluded. However, the action of the drug to selectively suppress the sinus node rate, and other data demonstrating no direct effect on myocardial contractility and systolic events, [16][17][18][19] suggest that UL-FS 49 may not have important direct effects on diastolic properties.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Accordingly, Guth et al (13) abolished the anti-ischemic effect of atenolol through atrial pacing during exercise-induced ischemia, suggesting that the negative inotropic effect of this ␤-blocker was negligible in this setting. Furthermore, zatebradine and ivabradine, two selective heart rate-reducing agents devoid of any negative inotropic effect, afforded significant anti-ischemic effects during exercise-induced ischemia in conscious dogs (12,18) and pigs (16). In contrast, Buck et al (2) reported only a partial attenuation of the beneficial effects of ␤-blockade on myocardial blood flow distribution and dynamic severity of a proximal coronary artery stenosis after atrial pacing.…”
mentioning
confidence: 99%
“…In all dogs, after coronary occlusion, systolic bulging appeared in the ischemic region. Ten minutes after coronary occlusion, UL-FS 49 (Karl Thomae, Biberach, the Federal Republic of Germany ([FRG]), 8 mg of a selective bradycardic agent (Kobinger and Lillie 1984;Dammgen et al 1985;Guth et al 1987;Indolfi et al 1989) were administered intravenously, and an additional dose of the drug (2 mg/each) was infused until the heart rate decreased to under 90 beats/minute (total dose: 8~14 mg), if necessary. About ten minutes later, the hemodynamic and segment lengths were stable.…”
Section: Protocolmentioning
confidence: 99%